All of us strangers [videorecording (Blu-Ray)] - Haigh, Andrew, 1973-; Scott, Andrew, 1976 October 21-; Mescal, Paul, 1996-; Bell, Jamie, 1986-; Foy, Claire, 1984-; Yamada, Taichi, 1934-2023 (Criterion collection, 2024)
A metaphysical exploration of queer love and loneliness, familial grief and healing, this delicate but audacious chamber drama confirms director Andrew Haigh's gift for bringing complicated emotions to the screen. Isolated in a seemingly empty new high-rise, London screenwriter Adam finds his solitary existence upended when he begins a passionate romance with the impulsive Harry, then reconnects with his parents in a reunion that pushes beyond the limits of time and space. Putting a deeply personal imprint on a novel by Japanese writer Taichi Yamada, Haigh reaches cosmic heights while never losing sight of the story's achingly human heart.